EVALUASI LAHAN UNTUK PENGEMBANGAN LAHAN PERKEBUNAN DI PULAU BACAN KABUPATEN HALMAHERA SELATAN - Sitti Wakiah; Johan A. Rombang; Johannes E.X. Rogi (Sam Ratulangi University, 2016)
The research objective was to determine the suitability of land for a certain class of agricultural crops, namely, vanilla, oil palm, coconut, cocoa, nutmeg and cloves and to determine the direction of the crop land use. The study used survey method and analysis is to compare with criteria data suitability of land for plantation crops. Based on the results obtained twenty eight overlay land units and land units nineteen taken as a sample. The results show the suitability of land in Bacan Island of South Halmahera District for commodity crop plantations vanilla, oil palm, coconut, nutmeg and cloves in a class of land suitability is quite suitable (S2), cocoa belongs to a class of land suitability is marginally suitable (S3) with limiting factor the relative humidity. Economic analysis for all commodities is very suitable for development and Bacan Island of South Halmahera Regency.